Comparison of Lignocaine with Ondansetron for Attenuation of Propofol Induced Pain in Adult Patient Undergoing Laparoscopic Cholecystectomy: A Comparative Randomized Study. - Kanojia, Akash; Sood, Rajesh; Kumar, Sandeep; Yadav, Rupesh (Journal of Anaesthesia and Pain, 2023)
Background: Propofol is a non-opioid intravenous anesthetic agent and it is most commonly used for induction of anesthesia but it has a consistent side-effect of pain when it is injected intravenously. Aim of our study was to compare lignocaine and ondansetron for attenuation of pain on propofol injection in laparoscopic cholecystectomy.Methods: 100 patients planned for laparoscopic cholecystectomy were enrolled for this comparative randomized study. Group L (Lignocaine) – Patients received Inj. Lignocaine 0.5 mg/kg 1 minute before inducing with injection propofol. Group O (Ondansetron) – Patients received Inj. Ondansetron 0.1mg/kg 1 minute before inducing with injection propofol. The patient was evaluated for pain during injection using a four-point scale of 5 seconds and 15 seconds after the propofol injection. Chi-squared test, Fisher’s exact test, and Mann-Whitney test were used for data analysis.Result: Demographic data  in group L and group O were similar. The mean± SD pain score during the first 5 seconds in group O was 0.38 ± 0.57 while in group L was 0.02 ± 0.14  (p<0.001). The mean± SD post-operative nausea and vomiting (PONV) score during the first hour in group O was 0.08 ± 0.27 while in group L was 1.96 ± 1.160 (p<0.001).Conclusion: We concluded that lignocaine was found more effective than ondansetron for attenuation of propofol-induced pain and post-operative nausea vomiting was much lower than by ondansetron as compared to lignocaine.